Strategi Manajemen Kinerja Karyawan Berdasarkan Kompetensi di Era Industri 4.0 - Siti Hanifah Hanum; Lilis Astika; M. Solih; Malik Ubaidillah; Tengku Darmansah (Journal of Creative Student Research, 2024)
The improvement of employee competencies is the key to organizational success in facing competition in the era of Industry 4.0. This research aims to formulate effective performance management strategies in developing employee competencies. this research uses a library study. Literature collection was conducted using free online databases such as Google Scholar, academia.edu, and researchgate.net. This article is categorized as a literature study, specifically a descriptive review. The research results indicate that effective performance management strategies must integrate competency development into all aspects of work, provide opportunities for employees to develop themselves, and create a work environment that encourages innovation and creativity.